POLICY IMPLEMENTATION ANALYSIS ON RABIES CONTROL IN BALI PROVINCE - Rimbawan, I Putu Dedy; Wahyuni, Made Dewi (Universitas Mahendradatta Denpasar, 2024)
Rabies or zoonotic disease is a very dangerous disease for warm-blooded animals and humans, so it receives very important attention from the government. This study aims to analyse the implementation of rabies control policies in Bali Province and to determine the influence of geographic information systems on the implementation of rabies control policies in Bali Province. This study uses qualitative research, data sourced from primary and secondary data with data collection techniques through observation and interviews, and using descriptive analysis. The results showed that cooperation with the private sector in the implementation of rabies control policies has been conducted and showed good results. Communication factors, human resources and authority, disposition, bureaucratic structure of the SOP showed good results, while budgetary resources and equipment resources were less than optimal. And the geographic information system has a positive impact, it just needs more socialisation to the community.